PENGARUH INISIASI MENYUSU DINI TERHADAP PRODUKSI ASI PADA IBU POST PARTUM DI RSKDIA SITTI FATIMAH MAKASSAR - Waode Isra Mira; Maria Sonda; Subriah Subriah; Indriani Indriani; Wirawati Amin (Sekolah Tinggi Pariwisata Mataram, 2023)
The Effect of Early Breastfeeding Initiation on the Production of Mother's Milk in Post Partum Mothers at the Siti Fatimah Makassar Special Regional Hospital for Children in 2019 guided by Djuhadiah Saadong and Maria Sonda. The effect of early breastfeeding initiation on breast milk production is the initiation of early breastfeeding carried out in the first hour. This will build up sucking sucking reflexes that stimulate the nerve endings around the breast to the front pituitary gland located at the base of the brain to produce the prolactin hormone. Prolactin will stimulate the breast to produce milk and can increase milk production. The study was conducted in May 2019 at the Siti Fatimah Makassar Special Regional Hospital for Children and Children. This type of research is quantitative with a Cross Sectional Study approach. The population in this study were all 291 people in postpartum mothers who were in the Special Hospital of Siti Fatimah Makassar and Children in Makassar. The samples were 72 people and were willing to be respondents with Purposive Sampling sampling techniques. The results showed that from 72 respondents who carried out early breastfeeding initiation as many as 50 respondents (69.4%) and those without as many as 22 respondents (30.6%), who experienced sufficient ASI production as many as 49 respondents (68.1%) and those who less than 23 respondents (31.9%). By testing using the Chi-Square technique obtained Ï =0.00 <of Î± = 0.05, this means that Ho is rejected and Ha is accepted. Thus there is an influence between early breastfeeding initiation and breast milk production in post partum mothers It is expected that midwives in implementing each care based on midwifery care so that they can identify problems and take action quickly and precisely, especially initiating early breastfeeding in facilitating breastfeeding